Real-world comparative outcomes of EGFR-TKIs for first-line treatment of EGFR+ metastatic non–small-cell lung cancer - Kibum Kim; Sakil Syeed; Trang Au; Amber Diaz; Matthew B. Schabath; Amanda Cass; Richard Hall; Lori Pai; Chenghui Li; Nicole Balmaceda; Alison Palumbo; Autumn Carey; et al. (Cancer Treatment and Research Communications)
Purpose: Osimertinib is a third-generation EGFR-TKI and preferred first-line (1L) treatment for EGFR positive (EGFR+) metastatic non-small cell lung cancer (mNSCLC). This study compared real-world clinical outcomes of 1L osimertinib versus 1st or 2nd generation EGFR-TKIs (1/2G-TKIs) in patients with EGFR+ mNSCLC. Methods: Nine academic cancer centers in the US participated in the retrospective cohort study. Patients aged ≥18 years with EGFR+ mNSCLC and treated with 1L EGFR-TKI were included. Clinical outcomes included real-world progression-free survival (rwPFS), duration of treatment (DOT), time to next treatment (TTNT), central nervous system incidence-free survival (CNS-IFS), and overall survival (OS). Multivariable regression models were used to control for differences in patient characteristics (p < 0.1) between the osimertinib and 1/2G-TKI cohorts. Results: The study included 181 osimertinib patients and 171 1/2G-TKI patients. Osimertinib had a longer rwPFS compared to 1/2G-TKIs (median PFS, 95 % confidence interval [CI]: 16.2 months (13.2–19.7) vs. 10.8 months (9.5–12.7); hazard Ratio [HR], 95 % CI: 0.60 (0.44–0.82). DOT and TTNT were significantly longer in patients treated with osimertinib versus 1/2G-TKI (HR, 95 % CI: 0.51 (0.38–0.68) for DOT; 0.54 (0.39–0.74) for TTNT). The respective HR point estimate for CNF-IFS and OS of 0.62 and 0.83 preferred osimertinib. However, small patient counts and number of events posed challenges in drawing conclusion regarding the significance of the delayed CNS-IFS or OS. Conclusion: Patients treated with osimertinib had a prolonged time to progression and longer time maintain the treatment compared to 1/2G-TKI. This real-world evidence is aligned with clinical trial results.